2018
DOI: 10.1098/rsos.171792
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability standards for carrier bags and plastic films in aquatic environments: a critical review

Abstract: Plastic litter is encountered in aquatic ecosystems across the globe, including polar environments and the deep sea. To mitigate the adverse societal and ecological impacts of this waste, there has been debate on whether ‘biodegradable' materials should be granted exemptions from plastic bag bans and levies. However, great care must be exercised when attempting to define this term, due to the broad and complex range of physical and chemical conditions encountered within natural ecosystems. Here, we review exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 87 publications
0
119
0
Order By: Relevance
“…Hartmann et al () included these as “plastics,” although others have excluded them due to their cellulose‐derived origin. Additionally, polyhydroxyalkanoate from bacterial precursors and polyactic acid from plant starch have recently been produced to be more inherently biodegradable (Harrison et al, ). The goal is to allow complete degradation to CO 2 after the end of product service life, as partial breakdown may generate intermediates of unknown properties, as well as microplastics.…”
Section: The Nature Of Plastics and Microplasticsmentioning
confidence: 99%
“…Hartmann et al () included these as “plastics,” although others have excluded them due to their cellulose‐derived origin. Additionally, polyhydroxyalkanoate from bacterial precursors and polyactic acid from plant starch have recently been produced to be more inherently biodegradable (Harrison et al, ). The goal is to allow complete degradation to CO 2 after the end of product service life, as partial breakdown may generate intermediates of unknown properties, as well as microplastics.…”
Section: The Nature Of Plastics and Microplasticsmentioning
confidence: 99%
“…To date, assessing the biodegradability of plastic has relied upon either composting approaches i.e., burying samples in soil, which have shown limitations in reproducibility 14,15 or samples being suspended in the sea, where samples risk being lost prior to recovery for quantification 25 . Our method allows the reliable assessment of plastic biodegradability via the quantification of CO2 produced in aqueous media as a direct result of microbial metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…"Bioplastics" can refer to polymer composites 14 and are marketed as a biodegradable alternative to LDPE. A. borkumensis was grown in liquid culture with a polymer composite, and CO2 production monitored over time.…”
Section: Monitoring Of a Borkumensis Growth On Plasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation and fate of single-use biodegradable plastics in natural environments are poorly understood (Harrison et al, 2018;Haider et al, 2019). Napper and Thompson (2019) found that biodegradable plastic carrier bags certified compostable disappeared completely from the marine environment within 3 months whereas they were still present after 27 months spent buried in soil.…”
Section: Introductionmentioning
confidence: 99%